Histidine metabolism drives liver cancer progression via immune microenvironment modulation through metabolic reprogramming - Liu, Pengcheng; Huang, Fuxin; Lin, Peixu; Liu, Jiayao; Zhou, Pincheng; Wang, Jie; Sun, Huanhuan; Xing, Fan; Ma, Haiqing (Journal of translational medicine, 2025)
Histidine metabolism is crucial in role in tumor biology, contributing to tumor progression, immune regulation, and metabolic reprogramming. In hepatocellular carcinoma (HCC), dysregulated histidine metabolism may promote tumor growth and immune evasion, although the specific mechanisms remain poorly understood. Using single-cell RNA sequencing, the expression patterns of histidine metabolism-related genes were evaluated across different cell types in HCC samples. In vivo and in vitro experiments were conducted to validate how histidine treatment affects macrophage and T-cell function. Furthermore, the TCGA database was utilized to construct a prognostic model to identify the key gene BUD23 and to examine its correlation with metabolism and immune infiltration. The proportion of parenchymal cells exhibiting high histidine metabolism was significantly increased, accompanied by a general reduction in immune and stromal cell infiltration. Notably, macrophages and T cells demonstrated impaired antitumor functions. In the high histidine metabolism group, multiple critical cell communication pathways (e.g., MIF, CLEC, MHC II) were downregulated, macrophages shifted toward immunosuppressive subpopulations, T cells exhibited an exhaustion phenotype, and CD8 + T-cell activation was diminished. Further in vivo and in vitro co-culture experiments confirmed that elevated histidine concentrations promoted M2 polarization in macrophages and weakened T-cell cytotoxicity, accelerating tumor proliferation. According to TCGA analyses, BUD23 was upregulated in the high histidine metabolism group and significantly negatively correlated with patient survival and immune cell infiltration. Silencing BUD23 boosted immune cell activation and cytotoxic effects, effectively reversing the immunosuppressive microenvironment. A multivariable Cox regression-based prognostic model indicated unfavorable outcomes in patients with high histidine metabolism. Histidine metabolism drives tumor cell metabolic reprogramming and reshapes the tumor immune microenvironment through intercellular communication, thereby promoting tumor progression. BUD23 shows promise as a biomarker for prognosis and immune response prediction in liver cancer. This study provides new therapeutic targets and theoretical support for liver cancer treatment by targeting histidine metabolism.